Transit economy: Kazakhstan trajectories - Aimurzinov, M.S.; Baimukhamedova, G.S.; Luchaninova А.А (BUKETOV BUSINESS REVIEW, 2019)
Since gaining independence in 1991 an issue of income inequality arised in the country. Sharp increase in income of people considered regional character of oil production boom. Author analyzed transition progress of Kazakhstani economy by drawing Lorenz curve and calculating Gini coefficient, as common methods of evaluating income inequality in economics. Also, author tested hypothesis of correlation between economic growth, increase in salaries and income inequality levels. After all calculations author concluded that country should closely monitor the expansion of oil field and oil-exploration. This has both direct and indirect effects on employment, inequality and overall growth of the economy in future. The government should be proactive in formulating macroeconomic policies, including tax reform, and creating trade opportunities beyond the hydrocarbon sector to improve income distribution. Investments in education in an active democratic environment will also further reduce income inequality. The current government’s economic policy commonly known as «Nurly Zhol» emphasizes on economic growth, role of finance, industry and overall social welfare. Tighter control of national funds, increased economic diversification, investment in human capital, and continuing development of financial sector are some of the key areas needing close attention to reduce inequality in Kazakhstan in the foreseeable future. Formation of a developed market economy in Kazakhstan is possible only with a developed strategy, considering not only the past and present periods of its social development but also the future, which should be based on objective conditions and principles of functioning of transition economies. On a final note, the government should closely monitor the expansion of oil field and oilexploration. This has both direct and indirect effects on employment, inequality and overall growth of the economy in future.